Cellular Immune Response to Parasitization in Drosophila Requires the EBF Orthologue Collier - Crozatier, Michèle; Ubeda, Jean-Michel; Vincent, Alain; Meister, Marie (PLOS Biology, 2004)
The lamellocyte is induced to differentiate under conditions such as parasitization by wasps and is shown in this study to require collier, the orthologue of the vertebrate early B-cell factor.